2022
DOI: 10.1061/(asce)wr.1943-5452.0001589
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Vulnerable Nodes, Impactful Viral Intrusion Sites, and Viral Infection Risk Reductions Offered by Chlorine Boosters in Municipal Drinking Water Networks

Abstract: The effects of drinking water system infrastructure on water quality and health following intrusion events have not been extensively studied. This study proposes a coupling of hydraulic and water-quality modeling with quantitative microbial risk assessment (QMRA) to characterize microbial infection risks. Two networks were considered based on their network configuration. We assumed a continuous intrusion of enterovirus under three scenarios. The location of vulnerable and influential nodes in a looped and a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Hydraulic and water quality modeling of these intrusion events has demonstrated that infection risks may be high for those affected when these events occur but that the spread of contamination in a municipal network may be highly heterogeneous . Modeling efforts have also demonstrated that risks may be higher for municipal networks in rural communities, which tend to be branched as opposed to looped, like networks for urban communities . Chemical contaminants can invade municipal networks, or they may be present as disinfection byproducts (DBPs), such as chloroform, bromodichloromethane, dibromochloromethane, and bromoform, which result from a reaction of hypochlorous or hypobromous acid with organic matter and pose potential cancer risks. , Private well water for drinking can also become contaminated with fecal pathogens and chemical contaminants due to failing septic systems and precipitation runoff .…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic and water quality modeling of these intrusion events has demonstrated that infection risks may be high for those affected when these events occur but that the spread of contamination in a municipal network may be highly heterogeneous . Modeling efforts have also demonstrated that risks may be higher for municipal networks in rural communities, which tend to be branched as opposed to looped, like networks for urban communities . Chemical contaminants can invade municipal networks, or they may be present as disinfection byproducts (DBPs), such as chloroform, bromodichloromethane, dibromochloromethane, and bromoform, which result from a reaction of hypochlorous or hypobromous acid with organic matter and pose potential cancer risks. , Private well water for drinking can also become contaminated with fecal pathogens and chemical contaminants due to failing septic systems and precipitation runoff .…”
Section: Introductionmentioning
confidence: 99%